PEMBUATAN AROMATERAPI DAN MINYAK URUT BERBASIS MINYAK ATSIRI TUMBUHAN SAPU-SAPU (Baeckea frutescens L.) - Nurhadini Nurhadini; Occa Roanisca; Verry Andre Fabiani (Universitas Mataram, 2026)
SMKN 1 Muntok, West Bangka, offers an Industrial Chemical Engineering vocational program that focuses on processing local raw materials into products with economic value. One underutilized local resource is the essential oil of the sapu-sapu plant (Baeckea frutescens L.), which grows abundantly in post-tin mining areas and is known to exhibit antibacterial, antifungal, and anti-inflammatory activities, making it a promising raw material for aromacare products. However, students’ limited knowledge of product formulation and marketing strategies remains a major constraint to its development. This community service activity aimed to enhance students’ knowledge and skills in producing safe, innovative, and competitive aromatherapy and massage oil products based on sapu-sapu essential oil. The methods included socialization of essential oil potential, training in product formulation and packaging in accordance with applicable standards, and digital marketing assistance through social media and e-commerce platforms, involving students from Universitas Bangka Belitung as facilitators. The results showed an improvement in students’ understanding of the potential of sapu-sapu essential oil, as well as their ability to formulate, package, and promote aromacare products. The resulting products had a distinctive aroma and were well accepted based on sensory evaluation. In addition, students began to recognize the importance of digital marketing in enhancing product competitiveness. Overall, this community service activity successfully improved students’ competencies in the production and marketing of aromacare products based on local potential and demonstrated the potential to generate flagship school products that support economic strengthening and student entrepreneurship.